Physical examination & health assessment / Carolyn Jarvis - Jarvis, Carolyn
High technology cannot replace the bedside assessment of the patient by the physician, argues Jarvis (a family nurse practitioner with Chestnut Health Systems). She presents the new edition of her textbook explaining health history-taking methods, physical examination skills, health promotion techniques, and clinical assessment tools. The edition adds chapters on domestic violence assessment, pain assessment, and the development of critical thinking skills. The CD- ROM contains case studies, video demonstrations, and printable patient health promotion guides. Annotation (c)2003 Book News, Inc., Portland, OR (booknews.com)